Kompetensi Kewirausahaan Para Knitting Entrepreneur Terhadap Kinerja Usaha (Kasus pada Sentra Industri Rajut Binong Jati Bandung) - Cut Irna Setiawati; Sasky Isnaeni Ahdiyawati (Benefit: Jurnal Manajemen dan Bisnis, 2021)
Abstract Micro, Small, and Medium Enterprises (MSMEs) as a business group that is proven to be able to survive in a situation of economic crisis. The existence of the ASEAN-China Free Trade Area agreement opens opportunities for MSME entrepreneurs to be able to develop but can also result in domestic products competing with products originating from China which is famous for its lower prices. This is also felt by knitting entrepreneurs at the Binong Jati Knitting Industry Center which can have an impact on the performance of their business. This study aims to see and analyze the relationship between financial competence and entrepreneurial competence on the business performance of non-knitting entrepreneurs at the Binong Jati Industrial Center, Bandung. This research uses quantitative methods and descriptive analysis methods. Sampling in this study is probability sampling with the type of simple random sampling with a number of respondents 78 knitting entrepreneurs in Binong Jati Rajut Industry Center. The data analysis method used in this study is Structural Equation Modeling (SEM) with data processing using SmartPLS. The results of this study indicate that entrepreneurial competence has a significant effect on the performance of financial ventures with a significant contribution of 59.4% and entrepreneurial competence also has a significant effect on non-financial business performance with a contribution of 45.8%.